IDEAL CONSTRUCTION REQUIREMENTS FORMIL EXPERT PROOF AS A BASIS OF JUDGE CONSIDERATION TO DETERMINE COUNTRY FINANCIAL DAMAGES IN CORRUPTION CRIMINAL ACTIONS BASED ON JUSTICE VALUES - Rosanto, Sera; Mashdurohatun , Anis; Soponyono, Eko (International Journal of Psychosocial Rehabilitation, 2020)
State losses can only be calculated by an expert. The experts here are not only experts in the field of financial audit but also technical experts who will calculate the feasibility of a building construction in the case of a criminal act of corruption which is related to the construction field. The expert who has the competence to calculate the quantity of a building and the price of a building is someone who has a construction management certification. Information from Construction Experts who do not have competence in corruption cases, then their statements become invalid. the purpose of this study is to analyze the weaknesses of expert statements as a basis for judges consideration in corruption, and to construct expert statements as a basis for judges in determining state losses in corruption based on the value of justice. weaknesses in expert evidence as a basis for judges to determine state financial losses in current corruption cases, namely, Weaknesses in Legal Substance, Weaknesses in Legal Structures, Weaknesses in Legal Culture. So that the provisions of Article 1 number 28 of the Criminal Procedure Code and Article 168 of the Criminal Procedure Code need to be reconstructed based on the values of justice.